Performing Sentiment Analysis with the Proposed Artificial Intelligence-Based Method Using Movie Commentaries - Yıldırım, Muhammed (Fırat University, 2022)
With the developing technology, social media, forum sites and blocks have been widely used. People are now using these channels very widely and they share their feelings and thoughts in these environments. Therefore, natural language processing applications have started to become a more popular topic with each passing day. One of the most popular topics in natural language processing is sentiment analysis. In sentiment analysis, subjective information is extracted by making examinations according to certain criteria. In this study, the IMDB data set was used to perform sentiment analysis. The IMDB dataset is one of the largest datasets on this subject, consisting of movie reviews. This dataset contains users' comments about movies. In the study, firstly, the data preprocessing step was carried out. Then, the prepared data set was classified in classical machine learning classifiers and the proposed ESA-based model. The proposed ESA-based model was more successful than the classical machine learning classifiers in analyzing the texts in the IMDB dataset, and the proposed deep model achieved an accuracy of 85.57%.

Gelişen teknoloji ile birlikte sosyal medya, forum siteleri ve bloklar yaygın bir şekilde kullanılmaya başlanmıştır. İnsanlar artık bu mecraları çok yaygın bir şekilde kullanmakta olup duygu ve düşüncelerini bu ortamlarda paylaşmaktadırlar. Bundan dolayı doğal dil işleme uygulamaları her geçen gün daha popüler bir konu haline gelmeye başlamıştır. Doğal dil işlemedeki en popüler konulardan birisi duygu analizidir. Duygu analizinde belirli kriterlere göre incelemeler yapılarak öznel bilgilerin çıkarılması sağlanmaktadır. Yapılan bu çalışmada duygu analizi yapmak için IMDB veri seti kullanılmıştır. IMDB veri seti, film yorumlarından oluşan bu konudaki en büyük veri setlerinden biridir. Bu veri seti kullanıcıların filmler hakkında ki yorumlarını içermektedir. Çalışmada, öncelikle veri önişleme adımı gerçekleştirilmiştir. Daha sonra hazırlanan veri seti klasik makine öğrenmesi sınıflandırıcılarında ve önerilen Evrişimsel Sinir Ağı ( ESA) tabanlı modelde sınıflandırılmıştır. Önerilen ESA tabanlı model IMDB veri setindeki metinleri analiz etme işleminde klasik makine öğrenmesi sınıflandırıcılarından daha başarılı olmuştur ve önerilen derin model %85.57 oranında bir doğruluk değeri elde etmiştir.
Film Yorumları Kullanılarak Önerilen Yapay Zekâ Tabanlı Yöntemle Duygu Analizinin Gerçekleştirilmesi
Keywords: Engineering; Mühendislik